Islamic Religion Education as an Instrument for Strengthening Character in an Era of Moral and Social Disruption - Hasan Basri, Tubagus (Al-Ilmu, 2025)
The rapid advancement of digital technology has created moral and social disruption, posing serious challenges for character formation among younger generations. Islamic Religious Education (IRE) is increasingly viewed as a strategic instrument to strengthen moral resilience and instill Islamic values in this context. This study aimed to design and evaluate a contextual, character-based IRE model that adapts to the realities of disruption. Employing a qualitative case study approach, data were collected through semi-structured interviews, focus group discussions (FGDs), classroom observations, and document analysis across three Islamic secondary schools in Indonesia. Thematic analysis revealed four key findings. First, differentiated learning supported by digital tools effectively fostered empathy, discipline, and responsibility among students. Second, teachers’ digital literacy competence was crucial in contextualizing Islamic values within contemporary challenges. Third, teacher role-modeling emerged as a strong determinant of students’ moral behavior, particularly in the digital domain. Finally, curriculum integration with digital citizenship education and collaboration with families and communities provided a sustainable framework for character building. The study concludes that an adaptive and contextual IRE model enhances honesty, empathy, responsibility, and digital ethics, equipping students to navigate the complexities of the digital era while maintaining their Islamic identity.